ANALISIS WACANA DALAM KARYA SASTRA (Analisis Strukturalisme Genetik dalam Novel Bilangan Fu) - Hatibie, Yunita (Jurnal Bahasa, Sastra, dan Budaya, 2024)
The research aims to analyze the discourse of genetic structuralism in the novel Bilangan Fu which is carried out in four stages. The first stage is the analysis of data related to the structure of Bilangan Fu through the relationship between characters and relationship of characters in their environment. The second stage is the analysis of the relationship between Ayu Utami's social life as the author and the novel Bilangan Fu. The third stage is the analysis of the historical background that created Bilangan Fu. The fourth stage is to find out the relationship between Ayu Utami's views on the sosial community (Indonesia) in Bilangan Fu. This research uses the genetic structuralism approach initiated by the Frenchman Lucien Goldman, a French literary expert who was later developed by Goldmann based on the ideas of Georg Lukacs. The source of data for this research is the novel Bilangan Fu by Ayu Utami published in 2008 by the Gramedia Popular Library, Jakarta, and secondary data in the form of books and articles related to novel Bilangan Fu. The conclusion in the discourse analysis of the novel Fu Number is to reflect Ayu Utami's views on the socio-economic-cultural-political-spiritualism situation of the Indonesian. The structure in Bilangan Fu is a part of integrated thinking framework and attitudes of Indonesian generaly. The author, the literary work, and the environment are interrelated factors in the emergence of a literary work, in this case the emergence of the novel Bilangan Fu.